2007
DOI: 10.1377/hlthaff.26.4.1096
|View full text |Cite
|
Sign up to set email alerts
|

Benefits For Employees With Children With Special Needs: Findings From The Collaborative Employee Benefit Study

Abstract: Approximately 13-15 percent of U.S. children have special health care needs.The demands of their caregiving can affect their parents' health and workplace performance. We interviewed forty-one U.S. employers and conducted focus groups with working parents in four U.S. cities to determine the extent to which employers understand the needs of these families and to identify opportunities for improving workplace benefits for these employees beyond health insurance. Employers saw value in improving workforce perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 6 publications
(5 reference statements)
0
26
0
Order By: Relevance
“…These findings may encourage employers' provision of benefit packages for families of CSHCN that include CC services and workplace support. 27 On the basis of our findings, doing so could foster a positive societal impact: retention of parents of CSHCN in the workforce. Recent estimates suggested that up to 40% of families with CSHCN experience financial burden, and this burden correlates with poor child health status.…”
Section: Discussionmentioning
confidence: 77%
“…These findings may encourage employers' provision of benefit packages for families of CSHCN that include CC services and workplace support. 27 On the basis of our findings, doing so could foster a positive societal impact: retention of parents of CSHCN in the workforce. Recent estimates suggested that up to 40% of families with CSHCN experience financial burden, and this burden correlates with poor child health status.…”
Section: Discussionmentioning
confidence: 77%
“…47 Although some innovative employers offer benefits that might support employees of children with disabilities, 48 having a child with a disability is still associated with reduced parental employment. Single parents of children with technology dependencies are 15 times more likely to quit employment secondary to care responsibilities at home than those in 2-parent families.…”
Section: Parents Of Children With Disabilities Need Financial Supportmentioning
confidence: 99%
“…Children with special health care needs also require more health services and specialized or adaptive care than healthier children, often without warning (Perrin et al, 2007). Mothers of children with ADHD experienced more difficulties in performing both their jobs and unpaid work, when compared to mothers of children with behavioral and non-behavioral problems (Hakkaart-van Roijen, Zwirs, Bouwmans, Tan, Schulpen, Vlasveld, & Buitelaar, 2007).…”
Section: Adhd and Maternal Employmentmentioning
confidence: 99%
“…Such benefits include flexible work schedules, on-site child-care, and paid maternity and paternity leave (Allen, 2001), with the option of a full-time job with a flexible schedule rated as the most valuable benefit offered by an employee. However, a recent study examining the extent to which employers understood the needs of families with special needs children indicated that many employers lack awareness of the scope or potential impact of what it means to have a child with special needs (Perrin et al, 2007). On a more positive note, these authors did find that employers were enthusiastic about expanding workers' use of benefits to accommodate the needs of this population.…”
Section: Flexibilitymentioning
confidence: 99%
See 1 more Smart Citation